2020
DOI: 10.1186/s43042-020-00102-3
|View full text |Cite
|
Sign up to set email alerts
|

The association between toll-like receptor 4 (TLR4) genotyping and the risk of epilepsy in children

Abstract: Background Epilepsy is one of the most widely recognized neurological disorders; unfortunately, twenty to thirty percent of patients do not get cured from epilepsy, despite many trials of antiepileptic drug (AED) therapy. Immunotherapy may be a viable treatment strategy in a subset of epileptic patients. The association between Toll-like receptor polymorphisms and epilepsy clarifies the role of the immune system in epilepsy and its response to the drug. Thus, this study will focus on the relation between TLR4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Alternatively, Siddiqui et al found an increase in 3435CC genotype frequency in DRE patients who were taking valproic acid [5]. The relationship between Toll-like receptor (TLR4) SNPs and resistance to various AEDs such as Na valproate, carbamazepine, clonazepam, phenytoin, and topiramate was examined by Abdelsalam et al, except for rs11536858 with clonazepam, no association was identified between the SNPs tested and drug resistance [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, Siddiqui et al found an increase in 3435CC genotype frequency in DRE patients who were taking valproic acid [5]. The relationship between Toll-like receptor (TLR4) SNPs and resistance to various AEDs such as Na valproate, carbamazepine, clonazepam, phenytoin, and topiramate was examined by Abdelsalam et al, except for rs11536858 with clonazepam, no association was identified between the SNPs tested and drug resistance [1].…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy is one of the most severe neurological chronic diseases, its types and response to drugs affected by multiple genetic polymorphisms in innate immunity receptors [1]. Despite its excellent prognosis, 20-30% of epileptic children were not cured of seizures, even with the various trials of antiepileptic drug (AED) therapy [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Brain derived neurotrophic factor ( Bdnf ) has antiseizure effects, however, infusion of BDNF can also lead to seizures [24, 45, 65, 92, 107]. Toll-like receptor 4 ( Tlr4 ) activation increases inflammation which can lead to seizures [1, 20, 37, 55, 122]. Glutamate decarboxylase 2 ( Gad2 ) converts glutamate into GABA, and loss of expression and activity of GAD2 is associated with seizure activity [18, 51, 132].…”
Section: Resultsmentioning
confidence: 99%
“…For rs1927911, there was no meaningful difference between drugresponsive and drug resistance or case/control groups. 374 The evidence is not limited to TLRs, and includes adaptor proteins as well. Villegas et al 375 showed a link between TRAF1/C5 Locus polymorphisms with seizures and clinical features in mexican cases with neurocysticercosis.…”
Section: Lithiummentioning
confidence: 99%